Factors Influencing Stockouts of Vital Category Drugs in the Pharmacy Facility, 2024 - Oqui, Maximiano; Corte-Real de Araújo, Artur Natalino; Esco-rial de Jesus Fernandes, Egia Clara da Costa; Evaristo Obeno, Olandino; Paicheco, Rosa; Freitas Moreira, Adriano (Rifa'Institute, 2025)
Introduction: Stockouts of vital medicines remain a critical issue in hospitals, particularly when drug availability drops to zero in pharmacy facilities. Although supplies may still exist elsewhere, it often takes up to a week for replenishment, potentially jeopardizing patient care. The